Modeling the Potential Distribution of Aulonemia queko: Historical, Current, and Future Scenarios in Ecuador and Other Andean Countries - Hugo Cedillo; Luis G. García-Montero; Omar Cabrera; Mélida Rocano; Andrés Arciniegas; Oswaldo Jadán (Diversity)
Aulonemia queko Goudot (Poaceae, Bambusoideae) is a species of great cultural importance that has been used as a non-timber forest product in Andean forests for centuries. Despite inhabiting montane forests vulnerable to deforestation, its distribution has not been thoroughly assessed for conservation. This study analyzes its potential distribution at the regional scale (the four countries where it is distributed) and locally (in greater detail within Ecuador), using presence records and climatic and land-use data. Maxent was identified as the best algorithm, achieving high values of AUC, TSS, sensitivity, and specificity. At a regional level, A. queko is estimated to occupy approximately 264,540 km2, mostly in Peru, with small areas in Bolivia. In Ecuador, the historical scenario showed the widest distribution, while the current–near-future scenario (20–40–SSP126) presented a more stable model. Temperature and rainfall represented critical factors in defining suitable habitats, as A. queko is highly sensitive to seasonal moisture availability. Land-use changes have reduced potential habitats by more than 35%, underscoring an intensified threat of habitat loss in these biodiversity-rich regions. However, projected climate changes pose an even greater impact, significantly reducing potential distribution. Our findings highlight the compelling effects of both climate-change-driven and human-driven land-use change on the future persistence of A. queko and emphasize the urgent need for targeted conservation strategies to protect its core habitats.